Optimization of via patterns for 0.13 micrometer copper dual damascene technology using phase shift mask - Chen, Hao. (2008)
The attenuated phase shifting mask has become very popular for printing via patterns in today’s semiconductor manufacturing industry. This is because this is suitable for patterns with any shapes. Also, it has an easier manufacturing technology. Its major disadvantage is the printability of side lobes due to the light that is transmitted through the dark areas.